Caputo Fractional Derivative Hadamard Inequalities for Strongly m-Convex Functions. (22nd April 2021) - Feng, Xue; Feng, Baolin; Farid, Ghulam; Bibi, Sidra; Xiaoyan, Qi; Wu, Ze
Abstract : In this paper, two versions of the Hadamard inequality are obtained by using Caputo fractional derivatives and strongly m -convex functions. The established results will provide refinements of well-known Caputo fractional derivative Hadamard inequalities for m -convex and convex functions. Also, error estimations of Caputo fractional derivative Hadamard inequalities are proved and show that these are better than error estimations already existing in literature.